2022
DOI: 10.3390/info13040177
|View full text |Cite
|
Sign up to set email alerts
|

A Game-Based Learning Approach in Digital Design Course to Enhance Students’ Competency

Abstract: Digital Design is a laboratory course, and the educator must focus on the students’ need to know why they study the theory and mainly on the transition from knowledge-based learning to competency-based learning. This study consists of five surveys that were conducted during 2017–2021. First, we evaluated students’ learning outcomes in order to define possible learning problems. According to the literature, gamification can have a positive impact on students’ motivation and learning outcomes. Therefore, we used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 60 publications
0
6
0
2
Order By: Relevance
“…This component also includes motivation to learn and use cognitive and metacognitive strategies in thinking and learning (Fredricks et al, 2016;Guo et al, 2020). Cognitive engagement is the involvement of students with the learning process of students in the class which ultimately shows that students are present not only physically but also their thoughts include attention, concentration, focus, participation and have a willingness to try to exceed the standards owned (Müller et al, 2021;Velaora et al, 2022). Finally this dimension looks at how students' efforts are needed in understanding and mastering a material then students achieve these abilities.…”
Section: Disccussionmentioning
confidence: 99%
“…This component also includes motivation to learn and use cognitive and metacognitive strategies in thinking and learning (Fredricks et al, 2016;Guo et al, 2020). Cognitive engagement is the involvement of students with the learning process of students in the class which ultimately shows that students are present not only physically but also their thoughts include attention, concentration, focus, participation and have a willingness to try to exceed the standards owned (Müller et al, 2021;Velaora et al, 2022). Finally this dimension looks at how students' efforts are needed in understanding and mastering a material then students achieve these abilities.…”
Section: Disccussionmentioning
confidence: 99%
“…Thus, Calderón et al [16] and Mohamad et al [17] found relations between student-centred digital technologies approach, intrinsic motivation, learning climate, and academic achievements. According to Velaora et al, student-centred learning experience fosters self-management in learning [18]. Clauss et al suggested Virtual Collaborative Learning concept to support student-centred online group work [19].…”
Section: Literature Reviewmentioning
confidence: 99%
“…En este contexto, según Holguin et al ( 2021) los procesos pedagógicos requieren que los docentes se capaciten no solo en el manejo de herramientas colaborativas, sino también, en la implementación de estrategias didácticas acordes al trabajo pedagógico remoto y así dar respuesta de acuerdo con Rodríguez y Avila (2022) a las exigencias inherentes al entorno pedagógico vigente, el cual requiere la movilización de habilidades para buscar y seleccionar información relevante de manera crítica hasta transformarla en conocimiento (Velaora et al, 2022).…”
Section: Análisis De Las Competencias Digitales En El Fortalecimiento...unclassified